COHESIVENESS OF THE WATU TELU ISLAMIC SOCIETY IN PRESERVING THE ESOT TANAK TRADITION - Zulhaiki Zulhaiki; Sukron Azhari; Muhammad Ali Fuadi; Masroer Masroer (Prodi Sosiologi Agama dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2024)
This study focuses on discussing the cohesiveness of the Wetu Telu Islamic community in the practice of the esot tanak tradition in Bangket Bayan. Peraktik the tradition of esot tanak is a tradition owned by the Wetu Telu Islamic community for generations. Even though the tradition has been around for a long time, the enthusiasm of the Wetu Telu Islamic community in carrying out the practice of the esot tanak tradition still exists until now. Although the development of the current era is able to shift the habits, especially the traditions of the community, it does not have an impact on the practice of the esot tanak tradition. The researcher uses a qualitative method with a phenomenological approach. As for data collection, the researcher uses three types such as, first, observation, in-depth interviews, and documentation. The results of this study show that the cohesiveness of the Wetu Telu Islamic community is formed on the basis of beliefs that have been passed down by their ancestors. The development of the times cannot be an obstacle for the Wetu Telu Islamic community in carrying out the tradition of esot tanak, because the values of their ancestors are always strong in their beliefs. This can be seen from the tradition of esot tanak which based on the beliefs of the Wetu Telu Islamic community is able to make their plants fertile and have an abundant harvest. In carrying out this tradition, it is required for the Wetu Telu Islamic community to always go together caused by the rules of the esot tanak tradition